2013
DOI: 10.4155/bio.13.37
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Bioanalysis and Biodistribution of Photosensitizer Conjugates for Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) was discovered in 1900 by Raab, and has since emerged as a promising tool for treating diseases characterized by unwanted cells or hyperproliferating tissue (e.g., cancer or infectious disease). PDT consists of the light excitation of a photosensitizer (PS) in the presence of O2 to yield highly reactive oxygen species. In recent years, PDT has been improved by the synthesis of targeted bioconjugates between monoclonal antibodies and PS, and by investigating PS biodistribution and PD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 56 publications
(71 reference statements)
1
26
0
Order By: Relevance
“…Actively targeting the PS to the tumor site by conjugation with a tumor specific antibody makes it possible to have high levels of the PS accumulate at the tumor cell surface with minimal binding to non-target sites [20]. Such strategies were developed and tested successfully in several in vitro and in vivo models [33,36,47]. Recently we developed a dye-immunoconjugate covalently linking the near IR absorbing water-soluble phthalocyanine derivative, IR700, to trastuzumab (antiHER2) or panatumumab (antiEGFR1) and showed that in tumor cells expressing the receptor selective cell death could be achieved with PIT, however, unconjugated IR700 had no effect [39].…”
Section: Discussionmentioning
confidence: 99%
“…Actively targeting the PS to the tumor site by conjugation with a tumor specific antibody makes it possible to have high levels of the PS accumulate at the tumor cell surface with minimal binding to non-target sites [20]. Such strategies were developed and tested successfully in several in vitro and in vivo models [33,36,47]. Recently we developed a dye-immunoconjugate covalently linking the near IR absorbing water-soluble phthalocyanine derivative, IR700, to trastuzumab (antiHER2) or panatumumab (antiEGFR1) and showed that in tumor cells expressing the receptor selective cell death could be achieved with PIT, however, unconjugated IR700 had no effect [39].…”
Section: Discussionmentioning
confidence: 99%
“…7 The toxicity and reactivity of ROS compounds cause damage to cell membranes, inhibiting cell division systems and breaking DNA cell chains. 8,9 Damaged cell membranes provide photosensitizer opportunities transplanted into cells, and thereby damaging organelles such as lysosomes, mitochondria, and nuclei. 10,11 For C. albicans cells, cell membrane damage caused by ROS compounds causes oxidative stress.…”
Section: Introductionmentioning
confidence: 99%
“…Serious shortcomings of this first PS (reviewed by Nyman and Hynninen [93]) stimulated intensive research into the development of compounds which can fulfill as many as possible of the formulated requirements for a good PS [94]. Significant success has been achieved in several aspects: (1) synthesis of stable PSs absorbing light in the red and NIR region of the spectrum (650-800 nm), which penetrates deeper into the tissues [52,95,96], (2) improvement of the selectivity (increasing the target/healthy tissue ratio) and (3) accelerating elimination from the body in order to reduce side effects [97,98,99,100]. Increased understanding of the mechanisms of the photodynamic action at cellular and molecular levels helped in formulating strategies for further improvement of PSs.…”
Section: Photosensitizersmentioning
confidence: 99%